Taxonomy of Knowledge Management in Open Innovations - Haapalainen, Päivi; Kantola, Jussi (My University, 2015)
This paper discusses knowledge management in an open innovation context. Open innovation is one of the most popular topics in innovation literature at the moment. Knowledge management is needed to enable inbound and outbound knowledge flows that define open innovation and to make sure that knowledge provided byan open innovation process can be used for successful business. The importance of knowledge is highlighted in the open innovation literature but the majority of the current literature only takes a narrow viewpoint of the issue and does not deal with knowledge management on the whole. The objective of this paper is to present a taxonomy of knowledge management in open innovation to provide an encompassing depiction of the phenomenon. The taxonomy was built on the basis of a broad literature review. The taxonomy will enrich academic discussion on the topic and could help companies to better design their open innovation strategy and process.
Keywords: Open innovation; Knowledge management; Taxonomy; fi=Tuotantotalous|en=Industrial Management|